Child education and work choices in the presence of a conditional cash transfer programme in rural Columbia - Orazio Attanasio; Emla Fitzsimons; Ana Gomez; Diana Lopez; Costas Meghir (Institute for Fiscal Studies (IFS), 2006)
The paper studies the effects of Familias en Acción, a conditional cash transfer program implemented in rural areas in Colombia since 2002, on school enrolment and child labour. Using a difference-in-difference framework, our results show that the program increased school participation of 14 to 17 year old children quite substantially, by between 5 and 7 percentage points, and had lower effects on the enrolment of younger children, in the region of 1 to 3 percentage points. The effects on work are largest in the relatively more urbanised parts of rural areas and particularly for younger children, whose participation in domestic work decreased by around 13 percentage points after the program, as compared to a decrease of 10 percentage points for older children in these same areas. The program had no discernible impacts on children's work in more rural areas. Participation in income-generating work remained largely unaffected by the program. We also find evidence of school and work time not being fully substitutable, suggesting that some, but not all, of the increased time at school may be drawn from children's leisure time.
Keywords: I28; I38; J22; O15; 330; Sozialpolitik; Öffentlicher Transfer; Kinderarbeit; Bildungsverhalten; Ländlicher Raum; Kolumbien